Natufian : kultura epipaleolityczna w dobie bliskowschodniej neolityzacji - Kościuk, Julia (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The Natufian culture occurs as direct genetic basis for the subsequent PPNA (PrePottery Neolithic A culture) – the unit with more common usage of agriculture as a mean of gaining food sources. As such, in the Natufian there could be traced social changes, leading to constitution of order among human groups, getting more attached to occupied lands. It seems, that mentioned period was crucial in process of formation of idea of ownership – possibly at the beginning in term of whole group, then evolving towards personal property
Keywords: Natufian; PPNA; neolithization; development of societies; Middle East